PENGARUH DUKUNGAN MANAJEMEN PUNCAK, KEMAMPUAN TEKNIK PERSONAL DAN KETERLIBATAN PEMAKAI TERHADAP KINERJA SISTEMINFORMASI AKUNTANS - Fazri Adhari (2021)
This research is using quantitative study that aims to investigate the effect of top management support, personal technical skills and involvement of users on accounting information system performance. The population and sample of this study were employees of coffee shop in south Tangerang and south Jakarta, amounting to 40 respondents. This study uses multiple linear regression statistical analysis of primary data using the IBM SPSS 28 program. Based on the results of testing all hypotheses, this study shows that partially variable top management support and involvement of users have a significant effect on the accounting information system performance and the variable personal technical skills have no effect significant on the accounting information system performance.